PENERAPAN STRATEGI PEMBELAJARAN SEARCH-SOLVE-CREATE-SHARE (SSCS) UNTUK MENINGKATKAN KEMAMPUAN PENGAMBILAN KEPUTUSAN SISWA SMA DALAM MEREDUKSI SAMPAH PLASTIK - Salma Nur Fauziyyah, - (2020)
Garbage is still a problem that has not been resolved until now. Meanwhile, with the increase in population, it will also follow the increase in the volume of landfills generated from human activities. This study aims to determine the application of SSCS learning strategies to improve the decision-making ability of high school students in reducing plastic waste, one of which is by making eco-bricks, so that the plastic waste can be managed properly. The research method used was quasy experimental research design with a Non-equivalent Control Pre-test and Post-test. This research was conducted on class X IPA students at SMA Negeri 1 Bandung as an experimental class that was given treatment using SSCS learning and the control class. The instruments used were open descriptions pre-test and post-test to measure decision-making abilities, student responses to learning, and learning implementation observation sheets. The results showed that there were differences in the decision-making ability of high school students. The experimental class with the SSCS learning strategy showed the average value of decision-making ability was higher than the control class. The conclusion of this study shows that the implementation of the SSCS learning strategy is proven to improve students' decision-making abilities on the topic of reducing plastic waste. Keyword: Search-Solve-Create-Share (SSCS) Learning Strategy, Decision-Making Skill, Reducing Plastic Waste, Ecobricks.